"Stirring Up the Crowd" May Be Protected Concerted Activity. Issue 4 (April 2015) - Unknown
Abstract : Michael Hershey was employed by Lou's Transport as a truck driver at a quarry in Michigan. Hershey and other drivers were dissatisfied with various aspects of their working conditions, including the safety of the unpaved roads within the quarry and the condition of their trucks.